2010
DOI: 10.1073/pnas.0914750107
|View full text |Cite
|
Sign up to set email alerts
|

Correlated physiological and perceptual effects of noise in a tactile stimulus

Abstract: We investigated connections between the physiology of rat barrel cortex neurons and the sensation of vibration in humans. One set of experiments measured neuronal responses in anesthetized rats to trains of whisker deflections, each train characterized either by constant amplitude across all deflections or by variable amplitude ("amplitude noise"). Firing rate and firing synchrony were, on average, boosted by the presence of noise. However, neurons were not uniform in their responses to noise. Barrel cortex ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…during visual categorization (288). Tactile responses in mouse barrel cortex require 200 ms to become differential (300). Similar multicomponent responses are seen with reward coding.…”
Section: Dopamine Event Detection Responsementioning
confidence: 66%
“…during visual categorization (288). Tactile responses in mouse barrel cortex require 200 ms to become differential (300). Similar multicomponent responses are seen with reward coding.…”
Section: Dopamine Event Detection Responsementioning
confidence: 66%
“…In both cases, subjects overestimated the intensity of the noisy vibrations compared with nonnoisy vibrations with the same mean values. When the same stimuli were applied to rat whiskers, barrel cortex neurons' firing rates were boosted by the presence of noise (40,41). The precise match of noise effects on barrel cortex firing rate and noise effects on perceived vibration intensity in human subjects again suggests that in the neuronal representation of a vibration, firing rate is the most salient firing property.…”
Section: Discussionmentioning
confidence: 87%
“…A different study showed that human subjects' judgment of vibrotactile intensity was affected by introducing temporal irregularity (frequency noise) and irregularity in deflection magnitude (amplitude noise) (40). In both cases, subjects overestimated the intensity of the noisy vibrations compared with nonnoisy vibrations with the same mean values.…”
Section: Discussionmentioning
confidence: 99%
“…First, in pilot studies, rats attended to noisy stimuli better than to periodic stimuli and were more likely await the go cue before withdrawing. Second, noisy vibrissal stimuli evoke a more robust cortical response (37,38), an advantage for future neurophysiological studies. Third, the structure of the noise stimulus is well suited to reverse correlation methods (39) and will provide rich data for studying the kinematic features extracted by sensory neurons (40,41).…”
Section: Discussionmentioning
confidence: 99%